Análisis de incidencias de la RED LAN, del GAD Municipal del cantón Montalvo - Sánchez Arreaga, Luis Leonardo (2021)
The present case study aimed to carry out an analysis of the incidents in the LAN network of the municipal GAD of the Montalvo canton, with the intention of detecting the existing problems both in the structured cabling, in the interconnection, and in computer support, once Once the problem has been recognized, seek a solution and be able to provide a quality of service. The difficulties in the infrastructure of the data network of the GAD of Canton Montalvo, are seen to be produced by not having an adequate wiring system for the communications data network, which is why security is not very reliable. Its installation is made up of UTP CAT5e cable, used in Ethernet-based LAN networks, being an industrial standard for computer networks and telephone systems of greater amplitude, on the other hand, the infrastructure does not have the physical and logical parameters, the state of computer equipment and devices are organized by bus-type topology. The descriptive research methodology was used, through which it was possible to determine and know the reality of the inconveniences that occur in the LAN network of the GAD of the Montalvo canton, likewise the techniques implemented were observation and survey, which was complemented with an observation card and the elaboration of a questionnaire of questions respectively. In the end, it was concluded that it is advisable to install a new and updated structured cabling, as well as to obtain the necessary interconnection devices, in order to adapt to using the safety standards and norms for improvements in data networks.